A Fully Aqueous Hybrid Electrolyte Rechargeable Battery with High Voltage and High Energy Density. Issue 40 (27th September 2020) - Yuan, Xinhai; Wu, Xiongwei; Zeng, Xian‐Xiang; Wang, Faxing; Wang, Jing; Zhu, Yusong; Fu, Lijun; Wu, Yuping; Duan, Xiangfeng
Abstract: Aqueous rechargeable batteries (ARBs) offer advantages in terms of safety, environmental friendliness and cost over their non‐aqueous counterparts. However, the narrow electrochemical stability window of water inherently limits the output voltage and energy density of ARBs. Here, a system with an aqueous hybrid electrolyte containing a Zn anode in alkaline solution and LiMn2 O4 cathode in neutral solution is reported. Combining the separated electrode‐electrolyte with a Li + ‐conducting membrane, the potential window is effectively widened to enable an aqueous hybrid electrolyte rechargeable battery (AHERB) above 2.3 V. This battery system delivers a steady energy density of 208 Wh kg −1 (based on the total weight of active materials) at 1.69 C with a high average output voltage up to 2.31 V, cycled for over 1000 cycles with an average Coulombic efficiency of >98%. Abstract : An alkaline‐neutral hybrid electrolyte system, which has a wide electrochemical stability window of 3 V, is assembled with a Li + ‐conducting membrane. Taking advantage of such an electrolyte system, an aqueous hybrid electrolyte rechargeable battery system (AHERBs) consisting of Zn anode and LiMn2 O4 cathode delivers a high average output voltage, high energy density, and excellent cycling performance.